Peran Kompensasi terhadap Motivasi dalam Menjaga Kinerja Guru Tidak Tetap di Lembaga Sekolah: Literature Review - Affandi Rahman Asmoro Rahayu; Ida Rindaningsih (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the role of compensation on the performance motivation of non-permanent teachers in educational institutions. Using the literature study method, this article discusses relevant literature on the role of compensation in improving teacher motivation and performance. Data were collected from national journals focusing on this topic, with keywords including the role of compensation, factors influencing compensation, and teacher performance. The results show that adequate compensation contributes significantly to the work motivation of non-permanent teachers, which in turn has a positive impact on their performance. This study recommends that educational institutions pay attention to a fair and transparent compensation system to improve the quality of teaching and the stability of non-permanent teachers' performance.